CTA Assessment of Midterm Morphological Changes to Chimney Grafts Used in the Treatment of Juxtarenal Aortic Aneurysms - Suteekhanit Hahtapornsawan (2020)
© The Author(s) 2019. Purpose: To evaluate chimney stent-graft position and morphological changes of the aneurysm sac as visualized by postoperative computed tomography angiography (CTA) over a minimum 24-month follow-up period. Materials and Methods: Twenty-one patients (mean age 75.7±8.6 years; 20 men) with juxtarenal aortic aneurysms who underwent successful chimney endovascular aneurysm repair (ch-EVAR) with the Endurant stent-graft and had 2 postoperative CTAs separated by at least 24 months were included in the study. CTA-based measurements of aortic stent-graft migration, target vessel angle, and chimney angle were compared between the serial scans. Results: During a mean follow-up of 34.9 months (range 24–69.2), the mean migration of the aortic stent-grafts was under 5 mm (2.76±2.4 mm). The average migration distance per year was 1.15 mm. The aneurysm diameter reduced a mean 3.25 mm (p=0.048). The right renal artery angle moved significantly upward 6.72° (p=0.025), while the right renal chimney stent-graft moved significantly downward 7.83° (p=0.042). The left renal artery angle also moved upward 1.87° (p=0.388) and the corresponding chimney moved downward 5.68° (p=0.133). During the study period, no type I/III endoleak or chimney occlusion was observed. Conclusion: Midterm morphometric assessment of ch-EVAR using CTA showed significant aneurysm sac shrinkage and a stable 3-year position of the abdominal devices, with the mean downward migration of the aortic stent-graft being <5 mm in the majority of cases. The chimney grafts seem to be prone to take an oblique rather than parallel configuration during follow-up. However, there was no relevant clinical consequence related to this phenomenon.